Model vadbe mišične hipertrofije in njegovi učinki na nekatere spremenljivke ravnotežja pri aktivnih starejših - Smajla, Darjan (Šport (Ljubljana), 2017)
The purpose of study was to determine whether a resistance training on fitness machines could increase muscle strength and improve balance in already active seniors. Fifteen persons older than 65 years (65+-4,6 let, 160,45+-8 cm, 68,74+-11 kg) volunteered in the study. They were participated in different supervised exercise programs at least twice per week prior the study. The training group met twice weekly for 8 weeks for training on fitness machines. Hypertrophy based strength training was designed to strengthen the muscles of the legs and body (core). Different strength and balance test were measured before and after training period. The results of the strength tests after training period showed statistically significant improvements in maximum torques of hip abductors, ankle extensors, and leg extensors. Results in functional reach tests significantly improved except in functional arm reach. During soft surface stance, statistically significant smaller movement of center of pressure was recorded. It was concluded that strength training on training machines can improve muscle strength in already physically active older persons. Strength is important for better balance also in this group of older persons.
Keywords: balance; mišična hipertrofija; mišična moč; muscle hypertrophy; muscle strength; ravnotežje; seniors; sport; starostniki; strength training; šport; vadba za moč